Structural dynamics and neural representation of wing deformation - Alexandra M. Yarger; Masateru Maeda; Igor Siwanowicz; Haruhiro Kajiyama; Simon M. Walker; Richard J. Bomphrey; Huai-Ti Lin (Proceedings of the National Academy of Sciences, 2025)
Locomotor control is facilitated by mechanosensory inputs that report how the body interacts with a physical medium. Effective representation of compliant wing deformations is particularly challenging due to the many degrees of freedom. Structural configurations can constrain the stimulus space, and strategic placement of sensors can simplify computation. Here, we measured and modeled wing displacement fields and characterized spatiotemporal encoding of the wing mechanosensors. Our data show how dragonfly wing architecture prescribes deformation modes consistent across models and measurements. We found that the wing’s state under normal flapping conditions is detected by the spike timing of few sensors, with additional sensors recruited under perturbation. The functional integration of wing biomechanics and sensor placement enables a straightforward solution for information transfer.